Bioprospecção de substâncias com potencial antitumoral em ascídias do litoral cearense : estudos com Eudistoma vannamei Millar, 1977 (Urochordata, Ascidiacea) - Jimenez, Paula Christine (2004)
The study, initially, evaluated the citotoxity of the hydro-alcoholic extracts of the 10 most abundant ascidian species from the coast of Ceará (Brazil), through the utilization of the following methods: brine shrimps lethality assay; development inhibition of sea urchin eggs; hemolytic potential, and inhibition of in vitro tumor cell growth. In three of the four assays performed, the Eudistoma vannamei species proved to be the most active one, and it was, therefore, selected for chemical and pharmacological characterization of its active principles. The extract was particionated by various solvents and fractionated by chromatography in silica gel 60 and sephadex LH-20 columns. The samples’ activities were monitored through the MTT method. Of the 60 collected samples, 15 were active. The IC50 of the 15 samples was evaluated through the MTT method, in 5 tumor cell lines: CEM, HL-60, MCF-7, HCT-8 e B-16. The fractions DCM-14 to DCM-18, derived from the CHCl2 phase and chemically very similar to each other, as indicated by CCDC, were the most active ones, presenting IC50 under 1,0 ug/mL in the majority of lines. The diketopiperazine 6-ethylamino-1-methyl-piperazine-2,5-dione was isolated from CHCl2 phase and identified as the major component, however, it was inactive upon cell proliferation. The H1RNM spectra of DCM 14 to DCM 18 fractions showed a number of compounds derived from that major diketopiperazine, which were not identified, as minor components. The study about the fractions effect upon HL-60’s viability (exclusion by trypan blue), proliferation (BrdU incorporation and growth curve) and cell death induction (cell morphology - H/E staining – annexin and BE/AO) revealed DCM-16 and 17 as the most potent cell proliferation reducers. DCM-16 displayed a pronounced BrdU uptake inhibitory effect, which may indicate interference in the DNA duplication process. DCM-17 showed a satisfactorily inhibition upon BrdU uptake, however, the apoptosis induction seems to be its main mode of action. DCM-14 and 15 also displayed a cell apoptosis inductor profile, while the latter indicated some signs of necrotic activity. The activities presented by these fractions are concentration and time dependent as longer periods with cell contact intensifies its citotoxic effect.